Limbah Masker di Era Pandemi: Kejahatan Meningkat atau Menurun? - Adhitya Pratama; Alisya Ameridya; Reza Ariesta Pudi; Shidiq Fickri Absyar (Program Studi Manajemen Lingkungan, 2021)
The COVID-19 pandemic in Indonesia has not only disrupted the national and economic sectors of the economy and health, but has also disrupted the environment, particularly those related to medical waste. Mask waste, which is one type of medical waste, has increased dramatically, and in severity it can also cause various adverse impacts on the environment as described through various previous studies. This paper aims to find out how the behavior of Indonesian people in waste mask waste is through social control theory, to find out the increase in crime rates caused by medical waste, and to find out whether there is a correlation between society behavior and the increase in environmental crime due to COVID-19. This paper uses a quantitative method, by conducting a survey of 100 productive age groups in Jakarta, Bogor, Depok, Tangerang, and Bekasi (Jabodetabek). The results showed that there was a significant correlation between society behavior in waste disposal and environmental improvement due to lack of control over waste disposal. Society's behavior in disposing of mask waste plays an important role in increasing the amount of medical waste as a form of environmental crime.